Genetic risk score is associated with vertical cup-disc ratio and improves prediction of primary open angle glaucoma in Latinos - Nannini, Drew R. (Ophthalmology, 2018)
PURPOSE: Genome-wide association studies have identified multiple genetic variants associated with vertical cup-disc ratio (VCDR). Genetic risk scores (GRS) examine the aggregate genetic effect of individual variants on a trait by combining these separate genetic variants into a single measure. The purpose of this study is to construct GRS for VCDR and determine whether the GRS are associated with VCDR and whether the GRS increase the discriminatory ability for primary open angle glaucoma (POAG) in a Latino population. DESIGN: Population-based genetic association study. PARTICIPANTS: A total of 4,018 Latino participants recruited from Los Angeles. METHODS: Weighted and unweighted GRS were constructed using 68 previously reported VCDR single nucleotide polymorphisms (SNPs), as well as SNPs from our own genome-wide association data. Linear and logistic regression analyses examined the associations of GRS with VCDR and POAG, respectively. To evaluate the discriminatory ability of the GRS for POAG, we conducted receiver operating characteristic (ROC) analyses. MAIN OUTCOME MEASURES: The relationship between GRS and VCDR in Latinos. RESULTS: The GRS were significantly associated with VCDR (P < 0.0001), after adjusting for age, gender, central corneal thickness, intraocular pressure, and education. The weighted GRS explained an additional 2.74% of the variation in VCDR. Adding the weighted GRS derived from previously reported SNPs resulted in a moderate improvement in the discriminatory ability for POAG during ROC analyses, yielding an AUC of 0.735 (95% CI: [0.701, 0.768]). When our own SNPs were used, the AUC significantly increased to 0.809 (95% CI: [0.781, 0.837], P < 0.0001). We obtained similar results for the unweighted GRS. CONCLUSION: To our knowledge, we are the first to report the association between GRS and VCDR, and its improvement in the discriminatory ability of POAG, in a Latino population.